2018
DOI: 10.1007/s12020-018-1663-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between CTLA-4 + 49A > G and – 318C > T single-nucleotide polymorphisms and susceptibility to thyroid neoplasm

Abstract: In this study, we observed that G allele in + 49 A > G and possibly lower expression of mutated CTLA-4 molecule, is associated with higher susceptibility to thyroid carcinoma. Although the G allele frequency was higher in thyroid cancer patients, when justified for the presence of lymphocytic thyroiditis, the presence of A allele seemed to increase the odds for PTC in patients with Hashimoto's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Subsequent study showed that the substitution of C to T modified the consensus sequence that binds lymphoid enhancing factor 1 (LEF1) and further altered the activity of the CTLA4 promoter (Chistiakov, Savost'anov, Turakulov, Efremov, & Demurov, ). Thus, it is rational that rs5742909 SNP, which affects the expression of CTLA4, would contribute to development and treatment outcome of various immune‐related diseases including tumours, whereas rs5742909 SNP was not associated either the risk of lung cancer, thyroid carcinoma and nasal NK/T‐cell lymphoma or treatment outcome of lung cancer and multiple myeloma (Abtahi, Izadi Jahromi, Dabbaghmanesh, Malekzadeh, & Ghaderi, ; Cheng et al, ; Lee et al, ; Ma et al, ; Qin et al, ). Similarly, rs5742909 SNP had no effect on the risk of ESCC and survival of patients with ESCC in the population from Cixian high‐incidence region.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent study showed that the substitution of C to T modified the consensus sequence that binds lymphoid enhancing factor 1 (LEF1) and further altered the activity of the CTLA4 promoter (Chistiakov, Savost'anov, Turakulov, Efremov, & Demurov, ). Thus, it is rational that rs5742909 SNP, which affects the expression of CTLA4, would contribute to development and treatment outcome of various immune‐related diseases including tumours, whereas rs5742909 SNP was not associated either the risk of lung cancer, thyroid carcinoma and nasal NK/T‐cell lymphoma or treatment outcome of lung cancer and multiple myeloma (Abtahi, Izadi Jahromi, Dabbaghmanesh, Malekzadeh, & Ghaderi, ; Cheng et al, ; Lee et al, ; Ma et al, ; Qin et al, ). Similarly, rs5742909 SNP had no effect on the risk of ESCC and survival of patients with ESCC in the population from Cixian high‐incidence region.…”
Section: Discussionmentioning
confidence: 99%
“…CTLA4 is a negative regulator of T-cell function and modulates the duration and strength of T cell mediated immune responses through several intrinsic and extrinsic mechanisms, triggering anergy and immune tolerance (27,28). Several studies have reported significant associations between frequent CTL4 polymorphisms and cancer susceptibility, including CRC (11,(29)(30)(31)(32)(33)(34)(35). We identified a positive association between CTL4 c.-319C > T (rs5742909) and CRC susceptibility (dominant genetic model, p = 0.023).…”
Section: Discussionmentioning
confidence: 99%